Perancangan Sistem Antrian Pasien Klinik Berorientasi Pengalaman Pengguna Dengan Metode Design Thinking - Muhammad Furqan Nazuli; rudiansyah; Athaillah Tri Naufaldo (BETRIK, 2025)
This study aims to design a patient queuing system in a clinic that is oriented towards user experience using the Design Thinking method. The main problems identified include long waiting times, unclear queue status information, and high administrative workload due to manual management. The Design Thinking approach is applied through five iterative stages: empathize, define, ideate, prototype, and testing. Based on the analysis of user needs for information transparency and ease of access, a web-based system prototype was developed with the main features of online registration without logging in, waiting time estimation, and real-time queue monitoring. The system evaluation involved 15 respondents using the System Usability Scale (SUS) instrument and resulted in an average score of 82.83, which is included in the Excellent (Grade A) category. This study provides practical contributions in the form of solutions for operational efficiency and transparency of clinical services, and provides academic contributions by enriching the health informatics literature regarding the effectiveness of implementing Human-Centered Design in overcoming barriers to technology adoption in primary healthcare facilities with limited resources.